Ad Palatinas acipensem mittite mensas: Fish remains from Viminacium - Zivaljevic, Ivana; Vukovic-Bogdanovic, Sonja; Bogdanovic, Ivan (Starinar (Beograd), 2019)
The paper presents the results of archaezoological analysis of fish remains from three locations at Viminacium (the Amphitheatre, Nad Klepeckom and Pirivoj), discussed jointly with finds of fishing equipment and relevant written sources on the subject. Albeit small and biased due to the hand-collection of animal bones, the fish faunal assemblage from Vimincium provides valuable data on the choice of exploited species, fishing and fish transportation practices, and patterns of consumption and deposition in the city and its surroundings. In addition to remains of locally available freshwater fish, occurring at all three sites, the Amphitheatre sample contained the remains of large anadromous sturgeons, possibly obtained from the downstream, Iron Gates area. Their size, contextual provenance, as well as their exceptional status according to written sources, indicates that there had been notable differences in access to high-quality fish among the different social classes at Viminacium.